Analisis Kuat Lentur Balok Laminasi Lengkung dengan Perekat Epoxy - Affan Annur Annaafi; Iskandar Yasin; M. Afif Shulhan (Universitas Muhammadiyah Surabaya, 2019)
AbstractVery large needs for woodhave an impact on the availability of wood which is decreasing every year, due to exploitation carried out on a large scale.Therefore it’s developed as a structure laminated components made by gluing several layers of wood or commonly called laminated beams or Glulam (Glued Laminated). This study used the experimental method by flexural test with one point loading. The dimensions of the object are 100 cm long, 2 cm wide, and by heigth variation 10 cm, 20 cm, 30 cm. Each variation used 3 specimens so there are 9 specimens. This specimens using epoxy adhesive. The results of the study showed that the flexural strength of the curved laminated beam with epoxy adhesive on an average load of 85.45 Kg and an average deflection of 23,510 mm. The result of laminated beam have maximum strength of 128.9 Kg with 17.27 mm deflection.Key words: Curved laminated beam, Flexural strength, deflection AbstrakKebutuhan kayu yang sangat besar berdampak pada ketersediaan kayu yang semakin berkurang setiap tahunnya akibat eksploitasi yang dilakukan secara besar-besaran. Maka dari itu di kembangkanlah bentuk struktur komponen kayu laminasi yang dibuat melalui perekatan beberapa lapis kayu atau biasa disebut dengan balok laminasi atau Glulam (Glued Laminated). Penelitian ini menggunakan metode eksperimen dengan melakukan uji lentur dengan beban satu titik. Dimensi benda uji balok laminasi lengkung memiliki panjang 100 cm , lebar 2 cm dan variasi tinggi 10 cm, 20 cm ,30 cm. Masing-masing variasi sebanyak 3 benda uji sehingga ada 9 benda uji. Balok laminasi menggunakan perekat epoxy. Hasil penelitian menunjukan bahwa kuat lentur balok laminasi lengkung dengan perekat epoxy mampu menahan beban rata-rata sebesar 85,45 Kg dan lendutan rata-rata 23,510 mm. Hasil pengujian lenturbalok laminasi mempunyai kekuatan maksimum 128,9 kg dengan lendutan 17,27 mm.Kata kunci : Balok laminasi lengkung, kuat lentur, lendutan